Community-Based Providers' Perspectives on Addressing Loneliness and Mental Health Services for Migrant Youth and Emerging Adults. Issue 49 (2nd January 2023) - Bessaha, Melissa; Persaud, Ushana; Asfe, Rukhsar; Muñoz-Laboy, Miguel
Abstract: Migrant youth and emerging adults (MYEA), ages 15 to 29, who recently migrated to the United States are vulnerable to experiencing chronic loneliness related to discrimination, social isolation, and stigma. Yet, there is limited intervention research on detecting, mitigating, and addressing the effects of chronic loneliness for MYEA. This study examined community-based providers' perspectives on the effects of social isolation and loneliness on MYEA, and the availability of social and mental health services for this population. This qualitative study utilized focus groups involving 18 providers serving MYEA in the New York metropolitan area. Data analysis involved double-coding by pairs of trained research team members to generate thematic codes. The main recurrent emerging themes were: (1) the importance of social-emotional wellbeing of MYEA; (2) the ways in which the experience of migration itself facilitated social isolation for MYEA; (3) the barriers to supportive services for mitigating chronic loneliness from an organizational perspective; and (4) the tensions between professional mandates and protections for migrant youth clients. Future intervention strategies, from an organizational perspective, must work through interorganizational partnerships building upon community assets to increase social connectedness to support migrant youth's social-emotional wellbeing through the transition to adulthood.